Affect-related synesthesias: a prospective view on their existence, expression and underlying mechanisms - Dael, Nele; Sierro, Guillaume; Mohr, Christine (Frontiers in Psychology, 2013)
The literature on developmental synaesthesia has seen numerous sensory combinations, with surprisingly few reports on synaesthesias involving affect. On the one hand, emotion, or more broadly affect, might be of minor importance to the synaesthetic experience (e.g. Sinke et al., 2012). On the other hand, predictions on how affect could be relevant to the synaesthetic experience remain to be formulated, in particular those that are driven by emotion theories. In this theoretical paper, we hypothesize that a priori studies on synaesthesia involving affect will observe the following. Firstly, the synaesthetic experience is not merely about discrete emotion processing or overall valence (positive, negative) but is determined by or even altered through cognitive appraisal processes. Secondly, the synaesthetic experience changes temporarily on a quantitative level according to i) the affective appraisal of the inducing stimulus or ii) the current affective state of the individual. These hypotheses are inferred from previous theoretical and empirical accounts on synaesthesia (including the few examples involving affect), different emotion theories, crossmodal processing accounts in synaesthetes and nonsynaesthetes, and the presumed stability of the synaesthetic experience. We hope that the current review will succeed in launching a new series of studies on “affective synaesthesias”. We particularly hope that such studies will apply the same creativity in experimental paradigms as we have seen and still see when assessing and evaluating “traditional” synaesthesias.